George Germain, Viscount Sackville, correspondence - Sackville, George Germain, Viscount, 1716-1785.
Letter (1779 June 3), written by Sackville relating to American loyalists in New York state.
British army officer and public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Great Britain. -- Army -- Colonial forces -- America; American loyalists -- New York (State); Great Britain -- Colonies -- America; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers, British; Public officials -- Great Britain